IMPLEMENTASI PENCANANGAN KAMPUNG PENGAWASAN PARTISIPATIF DI JAWA BARAT - Hilmi, Zaki (Jurnal Keadilan Pemilu, 2021)
The implementation of the General Election and Local Leader Election (Pilkada) requires the cooperation of numerous parties. One of them is by involving all community groups to be involved in supervision at every stage. Community involvement in elections is not only manifested in the form of people coming to polling stations and exercising their right to vote. One of the Election Supervisory Agency's (Bawaslu) mission is to encourage community-based participatory supervision. However, before reaching election supervision, community involvement in guarding democracy must first go through a process of socialization and the transfer of knowledge and skills in election supervision. The Participatory Monitoring Village is one of the national priority programs for participatory supervision that is being developed by the Election Supervisory Agency (Bawaslu) in West Java, where there is a group of people with the same area and concern for the progress of democracy and identical pioneering the monitoring village movement. The participatory monitoring village activities are comprised of two major components: the Citizens' Forum and Face-to-face Socialization by delivering materials on democracy, elections and participatory supervision. The community participates in the follow-up to these activities by monitoring and reporting fraud to the Election Supervisor.